Aquatic Plant Resources of Betana Wetland, Morang, Nepal - Niroula, B.; Singh, K.L.B (Our Nature, 2012)
A total of 84 aquatic plant species belonging to 71 genera and 41 families were recorded during January 2008 to December 2009 from Betana pond. They were classified into 7 growth forms as helophytes (22), tenagophytes (24), hyperhydates (23), epihydates (2), rosulates (3), vittates (6), and pleustophytes (4). Socio-economically useful plants included: medicinal (28 sp), wild food (19 sp), feed/fodder (28 sp), handicrafts (6 sp), and thatching (5 sp). DOI: http://dx.doi.org/10.3126/on.v9i1.5745